Efisiensi pasar dan mean-reversion di Indonesia - Sari, Dian Purnama; Maradesa, Djeini; Budiarso, Novi Swandari (Manajemen Bisnis dan Keuangan Korporat, 2024)
The Indonesian capital market is one of the markets in Asia that has the potential to be influenced by various economic and other global issues. This study aims to examine market conditions in Indonesia in the context of the weak form efficient market hypothesis. The sample used is the rate of return from the composite index in Indonesia with an observation period from 2010 to 2023. This study finds that the average value throughout the observation period is quite small and almost close to zero although it has an optimum return. In further analysis, the finding shows that the market in Indonesia is consistent with the weak form efficient market hypothesis with a mean-reversion tendency.